Lightweight steel roof trusses / Khalifah Hafizi Mohd Jamil - Mohd Jamil, Khalifah Hafizi (Universiti Teknologi MARA, Perak, 2015)
Roof is a very important structure to all building that will provide protection from weather and animal. This report will briefly describes about all the processes and method involved in the construction of the roof trusses. It is produced based on the experience in five months was placed at construction site. This report is divided into several parts and started with a company overview and background to the construction project. Observation found that the roof trusses construction is not as easy as it sounds. It involves a lot of parties and has complicated construction process. This report describes briefly the types and key components of a roof within more detail about the methods involved and used in the construction of trusses. In conclusion, this report will describe in detail the process and method of roof trusses construction in practice.